2012
DOI: 10.1080/13803395.2011.642849
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive correlates of nocturnal oxygen desaturation in a memory clinic population

Abstract: Previous studies suggested that sleep apnea is associated with neurocognitive impairments but did not examine populations most likely to have clinically relevant impairments. Cross-sectional, retrospective analyses were performed on 108 patients (65 with Mild Cognitive Impairment, 43 with dementia) seen in an academic medical center. Results indicated that severity of oxygen desaturation was associated with cognitive impairments in attention and executive function domains, even after controlling for age, sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
9
1
Order By: Relevance
“…This could explain why we did not find group effects but were still able to relate this parameter to this domain. Indeed, more severe falls in oxygenation could in part explain Yamout, Goldstein, Lah, Levey, and Bliwise's (2012) finding that the severity of oxygen desaturation was related to cognitive deficits (including performance in the Trails B measure of executive shifting) of patients with neurocognitive disorders, particularly those who had cardiovascular disease. The lack of significant changes in executive functioning in the present study and the pattern of mostly insignificant and small correlations with sleep parameters corroborate studies that have shown that OSAS patients are not necessarily cognitively impaired (e.g., Quan et al, 2006;Quan et al, 2011), despite being contradictory to other findings of impairment in different executive domains , which, however, were obtained with samples of mostly severe OSAS patients.…”
Section: Discussionmentioning
confidence: 95%
“…This could explain why we did not find group effects but were still able to relate this parameter to this domain. Indeed, more severe falls in oxygenation could in part explain Yamout, Goldstein, Lah, Levey, and Bliwise's (2012) finding that the severity of oxygen desaturation was related to cognitive deficits (including performance in the Trails B measure of executive shifting) of patients with neurocognitive disorders, particularly those who had cardiovascular disease. The lack of significant changes in executive functioning in the present study and the pattern of mostly insignificant and small correlations with sleep parameters corroborate studies that have shown that OSAS patients are not necessarily cognitively impaired (e.g., Quan et al, 2006;Quan et al, 2011), despite being contradictory to other findings of impairment in different executive domains , which, however, were obtained with samples of mostly severe OSAS patients.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence from similar areas of the study suggests that repeated episodes of oxygen desaturation are associated with impairment of attention and executive function. [ 5 ] It would be interesting to explore if cognitive changes associated with ECT have an association with the degree of desaturation. Furthermore, any damage occurring during ECT from these episodes of desaturation may not be apparent until late, when it is likely to be attributed to other causes.…”
Section: Discussionmentioning
confidence: 99%
“…Yamout et al [20*] reported that measures of nocturnal hypoxia were associated with cognitive impairment but that those relationships were limited to patients with comorbid medical disease. Additional data generated cross-sectionally from a memory clinic database of 405 (149 men; 256 women; mean [SD] age = 74.6 [9.1]) are presented in Table 1.…”
Section: Evidence Supporting An Association Between Impaired Cognitiomentioning
confidence: 99%
“…For these analyses, severe dementia was defined as a Mini-Mental State Exam score of ≤ 18. Cardiovascular disease (CVD) was defined in a manner similar to the approach described in Yamout et al [20*]: clinic measured systolic and/or diastolic blood pressure of > 140 or > 90 mm Hg, respectively; history of cardiovascular event (myocardial infarct, stroke, cardiac revascularization procedures); or use of cardiovascular medications (defined as diuretics, beta blockers, calcium channel inhibitors, ACE inhibitors). Likelihood of sleep apnea here was defined by self- or caregiver-reported snoring, defined using a previously validated snoring question [21].…”
Section: Evidence Supporting An Association Between Impaired Cognitiomentioning
confidence: 99%